Sistem Informasi Stok dan Penjualan Buku Berbasis Android di Penerbit Peneleh - Sila Sakti, Ciptagusti; Efrat Najaf, Abdul Rezha; Permatasari, Reisa (JITSI : Jurnal Ilmiah Teknologi Sistem Informasi, 2024)
In the current era, technology developments are very fast. Many businesses start to update their business processes by utilizing technology that can facilitate their organization's business processes. Penerbit Peneleh carry out sales activities for their published books. This research discusses the design and development of a Book Stock and Sales Information System at Penerbit Peneleh which can help them monitor book stock, record sales, and compile information about printing prices and selling prices of books efficiently. The development method used is the waterfall model with data collection through interviews with the organization. The result of this research is an Android application that is integrated with a barcode scanner and Google Books API which can help organizations run their business.